Long-term effects of mineral precipitation on process performance, granules' morphology and microbial community in anammox granular sludge. Issue 1 (February 2022) - Polizzi, C.; Lotti, T.; Ricoveri, A.; Campo, R.; Vannini, C.; Ramazzotti, M.; Gabriel, D.; Munz, G.
Abstract: When treating wastewaters prone to inert precipitation with granular sludge systems, mineral formation needs to be properly controlled to ensure system's long-term stability. In this work, an extensive study on mineral precipitation on the surface of anammox granular sludge is presented. A 7-L reactor was inoculated with one-year stored biomass and volumetric load up to 0.48 gN-NO2 - /l/d were achieved, with nitrite removal above 95% and total nitrogen removal rate of almost 1 gN/l/d. Severe mineral precipitation was observed on the granules' surface after three months of hard-water feeding and resulted in a dramatic deterioration of reactor performance and biomass activity. Substrate diffusion limitation in the inner layers, insufficient mixing due to higher granule density and biofilm erosion due to shear stress increase were deemed the main mechanisms that lead to progressive process disruption. Gravimetric selection was applied to discard granules affected by precipitation and allowed for process restoration. Microbial community analyses revealed that mineral composition possibly affected competition between " Ca . Brocadia" and " Ca . Kuenenia". The knowledge gathered in the present study details the dramatic consequences on process performance lead by severe mineral precipitation and it is presented as a warning for full-scale applications treating wastewaters prone to precipitation. Graphical Abstract: ga1 Highlights: Fast start-up was obtained using seeding sludge after 1-year storage. Mineral formation in granules' surface resulted in substrate diffusion limitation. Microbial community was affected by mineral precipitation. Gravimetric selection and solids monitoring are effective for inert control.